Experience and Spiritual Meaning of Cervical Cancer Patients with Chemotherapy - Supatmi , Supatmi; Santoso, Budi; Yunitasari, Esti (International Conference on Sustainable Health Promotion, 2021)
In health crises such as the diagnosis of cervical cancer by the chemotherapy, spirituality has a major role in this process, by providing calmness and giving meaning to the disease. A spiritual Muslim provides guidance through concepts and values that provide strategies for overcoming illness and finding meaning in life. Aims: This study aims to describe spiritual meaning, as one of the components of psychological understanding inherent in the lives of cervical cancer patients with chemotherapy. To illustrate the experience and spiritual meaning of 13 Muslim patients diagnosed with cervical cancer who received chemotherapy were interviewed at Dr. Soetomo's hospital, and qualitative data with thematic analysis.  One's confidence about the spiritual meaning of his or her disease experience can make people patient, tawakal and also continue to strive for healing. Strategies to provide spiritual care are included in the treatment guidelines and there is a need for cooperation between interdisciplinary health teams, including doctors, and nurses of all team members who provide care